2017
DOI: 10.1016/s2352-4642(17)30014-7
|View full text |Cite
|
Sign up to set email alerts
|

Approaching the third decade of paediatric palliative oncology investigation: historical progress and future directions

Abstract: Paediatric palliative care (PPC) endeavours to alleviate the suffering and improve the quality of life of children with serious illnesses and their families. In the past two decades since WHO defined PPC and called for its inclusion in paediatric oncology care, rigorous investigation has provided important insights. For example, the first decade of research focused on end-of-life experiences of the child and the family, underscoring the high prevalence of symptom burden, the barriers to parent–provider concord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
49
0
12

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 103 publications
0
49
0
12
Order By: Relevance
“…Rosenberg et al . concluded that the resilience of young people recently diagnosed with cancer is directly associated with their personal resources and learned abilities: stress management, goal‐setting, positive reframing, searching for benefits, social support, and maintaining relationships with relatives and peers . One recent study on depression in cancer survivors found no difference in the rates of clinically relevant depression between the younger and older adult cohorts, although there was a trend toward more depression among the younger patients.…”
Section: Discussionmentioning
confidence: 99%
“…Rosenberg et al . concluded that the resilience of young people recently diagnosed with cancer is directly associated with their personal resources and learned abilities: stress management, goal‐setting, positive reframing, searching for benefits, social support, and maintaining relationships with relatives and peers . One recent study on depression in cancer survivors found no difference in the rates of clinically relevant depression between the younger and older adult cohorts, although there was a trend toward more depression among the younger patients.…”
Section: Discussionmentioning
confidence: 99%
“…Pediatric cancer remains a life‐changing diagnosis with substantial prognostic uncertainty and high caregiving demands; affecting both children/adolescents as well as their parents who usually provide extensive care . Studies have shown that these family caregivers (FCs) are subjected to physical and psychological burden during and after their children's medical care …”
Section: Introductionmentioning
confidence: 99%
“…1 Studies have shown that these family caregivers (FCs) are subjected to physical and psychological burden during and after their children's medical care. [2][3][4][5] In fact, caregivers of pediatric cancer patients are at high risk for developing different types of somatic complaints 2,4,6 and higher levels of inflammatory markers (eg, cortisol and C-reactive protein). 7 It is estimated that 20% to 66% of FCs present with significant depressive symptoms, 6,8 and 20% to 30% of caregivers are at high risk for psychiatric morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…Children who receive timely subspecialty PPC services at the end of life experience more comprehensive and successful pain and symptom assessment, fewer invasive procedures, and more documentation regarding advance care plans when compared to children who do not receive subspecialty PPC . In contrast, late PPC referrals translate to missed opportunities for patients and families to prepare for the end of life, in turn leading to increased child suffering and increased psychological distress among parents and surviving siblings . Involving subspecialty PPC neither negates nor replaces the role of pediatric oncologists.…”
mentioning
confidence: 99%
“…Barrier #3: “Pediatric oncologists are unaware of the potential benefits and scope of PPC.” Although the evidence‐base supporting the scope and potential benefit of PPC is well established, pediatric oncologists may be unfamiliar with PPC research. Reasons include the overwhelming volume of medical literature with which they must keep up to date (their attention is directed to cutting edge biomedical studies), as well as an inherent bias to alternative types of science (the perception that PPC scientific findings are less compelling than classic laboratory‐based experiments or drug‐treatment clinical trials).…”
mentioning
confidence: 99%